Comparison of jumping and anaerobic performance in Turkish and Cypriot professional soccer goalkeepers - Acar, M.; Keles, C.; Balyan, M.; Özkol, Z.; Karamizrak, O. (Journal of Sports Sciences, 2004)
Ziel der Studie war die Untersuchung des Verhältnisses verschiedener Sprünge mit alaktaziden und laktaziden Kapazitäten bei Profi-Fußballtorhütern.